Clinico-pathological profile of breast cancer patients in a radiation therapy centre - Rahman, M. Masudur; Shams, Mohammad Jahan; Haque, Mostafa Sanaul; Biswas, Shourov (International Journal of Research in Medical Sciences, 2024)
Background: The aim of the study was to evaluate the clinico-pathological characteristics of patients with breast cancer at the Radiation Center of Bangabandhu Sheikh Mujib Medical University (BSMMU), a tertiary‑care cancer center in Dhaka, Bangladesh. Methods: This descriptive study was conducted from March 2021 to February 2022 where patients receiving radiotherapy for breast cancer were included. Data were collected from face-to-face interviews with patients and from their investigation reports. Data regarding age, presenting symptoms, histological type, tumor size, involvement of regional nodes, hormonal receptor status, and human epidermal growth factor receptor 2 (HER2) amplification were recorded and then analyzed. Results: The mean age of the patients was 52.53 years. Most of the patients (93%) were multiparous and 62.24% were postmenopausal. The most common symptom was breast lump (91.6%). Infiltrating ductal carcinoma and lobular carcinoma were seen in 136 (95.1%) and 7 (4.9%) cases respectively. The TNM stage distribution was stage I, 6 (4.2%); stage II, 52 (36.36%); stage III, 76 (53.15%); and stage IV, 9 (6.29%). Locally advanced breast cancer constituted 42.66% of the cases. Among the patients 90 (62.94%) patients were ER/PR positive and 42 (29.37%) patients were HER2 positive. Triple negative breast cancer (TNBC) constituted 25.17% (36) of the study population. All receptors were positive in 25 patients (17.48%). Conclusions: Majority of our patients receiving breast radiotherapy at our center are middle aged and have advanced disease. TNBC and HER2 positive breast cancer are more common in our population.